Development of simple and accurate detection systems for Cannabis sativa using DNA chromatography. (October 2018) - Yamamuro, Tadashi; Miyamoto, Shigehiko; Kitamura, Masashi; Muro, Tomonori; Iwata, Yuko T.; Segawa, Hiroki; Kuwayama, Kenji; Tsujikawa, Kenji; Kanamori, Tatsuyuki; Inoue, Hiroyuki
Abstract: In recent years, the need for analyzing cannabis DNA has increased in order to accommodate the various types of cannabis samples encountered in forensic investigation. This study was aimed to establish a simple and accurate cannabis DNA detection system using DNA chromatography. Two chromatography chip systems with different features were successfully developed. One system (the "four-line version") involves tetraplex PCR amplification, which could be used to detect cannabis DNA and distinguish between drug-type and fiber-type cannabis using the tetrahydrocannabinolic acid synthase gene sequence. The other system was the "three-line version" with triplex amplification, which was specialized to distinguish cannabis from other plants, and had a sensitivity (10 fg DNA/reaction) that was 100 times greater than the four-line version. In both versions, no false positives were observed for 60 medicinal plants, and accurate detection could be performed for several simulated forensic samples such as cannabis leaves, buds, stems, roots, seeds, resin, and cannabis leaves blended 1/100 in tobacco. Detection could be performed by the naked eye and only a thermal cycler was required for operation. Thus, DNA chromatography systems for cannabis detection are expected to contribute to the analysis of cannabis DNA in forensic chemistry laboratories without extensive equipment.